2006
DOI: 10.1152/ajplung.00266.2006
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights into acute inflammatory lung injury

Abstract: Acute lung injury (ALI) is a devastating syndrome (usually associated with sepsis) that represents a major healthcare burden in the United States. We have focused our studies on unraveling the genetic underpinnings of this syndrome utilizing a candidate gene approach to identify novel genes for ALI susceptibility. Two novel genes identified by this approach include pre-B cell colony-enhancing factor (PBEF) and the gene for myosin light chain kinase (MLCK). PBEF protein levels were elevated in human bronchoalve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 30 publications
(27 reference statements)
1
20
0
Order By: Relevance
“…Serum IL-6 and TNF-α levels were higher in ZDF rats, and their mRNA expression in liver tissue was significantly increased. Some reports have suggested that both tissue and circulating visfatin levels are increased in inflammatory disorders [9][10][11]. It has been shown that FFAs play a significant role in hepatic inflammation and insulin resistance [4] and that the liver secretes visfatin [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum IL-6 and TNF-α levels were higher in ZDF rats, and their mRNA expression in liver tissue was significantly increased. Some reports have suggested that both tissue and circulating visfatin levels are increased in inflammatory disorders [9][10][11]. It has been shown that FFAs play a significant role in hepatic inflammation and insulin resistance [4] and that the liver secretes visfatin [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that visfatin has nicotinamide adenine dinucleotide (NAD) biosynthetic activity; and thus, visfatin is also known as nicotinamide phosphoribosyltransferase, the rate-limiting enzyme that converts nicotinamide to nicotinamide mononucleotide, a NAD precursor [8]. Recent studies have demonstrated that visfatin acts as a proinflammatory cytokine and that its expression is increased in inflammatory conditions such as acute lung injury, sepsis, and rheumatoid arthritis [9][10][11]. Visfatin is associated with obesity and obesity-related insulin resistance, type 2 diabetes mellitus, and metabolic syndrome [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…We previously used genomics-intensive approaches to identify potential ALI and VILI susceptibility candidate genes (11,12). We determined that the gene encoding pre-B-cell colony enhancing factor (PBEF), a proinflammatory cytokine expressed in amniotic membranes during gestation (13), represented a potential VILI candidate gene and novel biomarker in sepsis and ALI (1).…”
mentioning
confidence: 99%
“…It exerts chemotactic activity and up-regulates the serum levels of other pro-inflammatory cytokines [110]. Garcia and Vinasco demonstrated a crucial role for PBEF in acute lung injury (ALI), which is usually caused by sepsis [111]. In these critical ill patients they found elevated concentrations of PBEF in bronchoalveolar lavage and serum.…”
Section: Visfatinmentioning
confidence: 99%